Parental Interactions Associated with Adolescent Health Risk Behavior: Premarital Sexual and Aggressive Behavior - Ilya Krisnana; Praba Diyan Rachmawati; Iqlima Dwi Kurnia; Nur Sayyid J Rummy (Universitas Airlangga, 2021)
Introduction: Interactions within the family will determine the behavior of adolescents. Lack of interaction in adolescents is a risk factor for adolescent behaving deviant, among others, unmerried sexual and aggressive behaviors. The purpose of this study was to analyze the relationship between parental interaction and the premarital sexual and aggressive behavior among adolescents.Methods: A cross-sectional approach was taken. The sample consisted of 744 adolescents from junior high school and senior high school in Java Island aged 13 - 19 years old who had completed a Google form. The independent variable was parent interaction while the dependent variable was premarital sexual and aggressive behaviors. The PACHIQ-R questionnaire was used for measuring parent interaction. While the dependent variable was using checklist questionnaire. The data was analyzed using Spearman Rank correlation with a level of significance α=0.05.Results: The results show that there is a correlation between the parent interactions and premarital sexual (p=0.007; r=0.100) and aggressive behavior among adolescents (p=<0.001;r=0.156). Parental interaction has an association on the adolescent’s behavior, especially in terms of premarital sexual and aggressive behavior.Conclusion:Nurses need to provide education not only to parents, but also for adolescents to prevent premarital sexual and aggressive behaviors among adolescents in any media that available.